A scoping review of children's experiences of residential care settings in the global South. (October 2019) - Roche, Steven
Abstract: Residential Care Settings (RCSs), including orphanages, children's homes, and institutional care, form a significant welfare response in communities across the global South. Given their scale, central role in welfare provision, and the potential harms to children and young people who live in them, a greater understanding of their functions, circumstances, and how they are conceptualised and experienced by children is critical. This scoping review explores available peer-reviewed articles on children's experiences of residential care settings in the global South. A comprehensive search of ten databases was conducted, and 27 articles included in the review. The study finds that models of RCSs are diverse and highly contextual, with children articulating distinct experiences and perspectives of RCSs in the global South. Children express generally positive views towards their RCSs, emphasising a highly relational life, with large peer networks and community connections. They also draw attention to the material benefits of RCSs in comparison to prior care with family, and educative opportunities that they provide. Challenges include maintaining relationships with family, constraints on their agency in day-to-day life, as well as navigating disruption around identity and belonging, indicating clear areas for policy and practice development that may improve family relationality and reduce social exclusion. Highlights: Children articulate distinct experiences and perspectives of RCSs in the global South Children in residential care settings express a highly relational life. Children provide generally positive views of RCSs. A major challenge for children are constraints on family and community relationships. Detailed life histories of children in residential care settings are lacking in the literature.